Impact of biopsy perineural invasion on the outcomes of patients who underwent radical prostatectomy: a systematic review and meta-analysis. (3rd September 2019) - Wu, Shulin; Lin, Xueming; Lin, Sharron X.; Lu, Min; Deng, Tuo; Wang, Zongwei; Olumi, Aria F.; Dahl, Douglas M.; Wang, Dongwen; Blute, Michael L.; Wu, Chin-Lee
Abstract: Objectives: To investigate the association between biopsy perineural invasion (PNI) and oncological outcomes of prostate cancer (PCa) after radical prostatectomy (RP). Materials and methods: A systematic literature search was performed using PubMed, EMBASE and Web of Science up to December 2018 to identify the eligible studies that included localized PCa patients who underwent biopsy and subsequently RP as well as follow-up information. Meta-analyses were conducted using available hazard ratios (HRs) of biopsy PNI from both univariate and multivariate analyses. Results: Eighteen studies including 14, 855 patients with treatment follow-up information were included in the current systematic review. The rate of biopsy PNI varied between 7.0% and 33.0%. Seven out of the 18 studies that demonstrated biopsy PNI were associated with adverse pathologic features. Thirteen out of the 18 studies showed biopsy PNI correlated significantly with higher rates of biochemical recurrence (BCR)/cancer progression status or worse prognostic outcomes. With pooled data based on four studies with available univariate analysis results and four studies with multivariate analysis, statistically significant associations were found between biopsy PNI and BCR with univariate analysis (HR = 2.05; 95% CI = 1.57–2.68; p  < 0.001) and with multivariate analysis (HR = 1.57; 95% CI = 1.28–1.93; p  < 0.001). Conclusion: Evidence from the included observational studies indicated that biopsy PNI was not only correlated with adverse pathologic characteristics but also with worse BCR prognosis of local PCa after RP. The status of biopsy PNI could serve as a promising risk-stratification factor to help the decision-making process, considering active surveillance (AS) or further treatment for PCa patients.